Detection of Lard in Animal Fat Mixtures Using ATR-FTIR Fingerprint and SPME-GC/MS-Based Volatilomics - Putri, Silmiyah; Budi, Faleh Setia; Suseno, Sugeng Heri; Heryani, Heryani; Ramadhan, Muhamad Fauzi; Regiyana, Yane; Yuliana, Nancy Dewi (Universitas Gadjah Mada, 2024)
This study aims to detect the presence of lard in several halal animal fats (beef, chicken, and goat fat) based on their infrared fingerprint and volatile compound profile (volatilomics). A mixture of fat samples obtained from halal animals and lard at different concentrations (0, 20, 40, 60, and 80%, v/v) were subjected to attenuated total reflection-Fourier transformed infrared spectroscopy (ATR-FTIR) and solid phase microextraction coupled to gas chromatography-mass spectrometry (SPME-GC/MS) analysis, respectively. The data was processed using orthogonal projection to the least square–discriminant analysis (OPLS-DA). The results showed that ATR-FTIR could only identify the presence of lard in chicken fat up to the lowest concentration used in this study (10%) but failed in other fat samples. SPME-GC/MS detected the presence of lard in all animal fats up to the lowest concentration added (10%). The results of this study revealed that the volatilomics technique had more potential to be developed as a basis for the rapid detection of halal and non-halal animal fat than the infrared fingerprint. This study also emphasized that markers of non-halal animal fats can be different when the same fats are added to different food products.